# A + AB gets simplified to

By BYJU'S Exam Prep

Updated on: September 25th, 2023

1. A + B
2. AB
3. A
4. B

Let us take x = A + AB

Taking A common in the above expression, we get: F = A (1 + B)

1 + Any Variable is always 1 in Boolean Algebra.

Therefore, F = A.

Table of content

## Answer: After Simplification, A + AB will be equal to A.

 Name OR Form AND Form Null Law 1 + A = 1 0.A = 0 Identity law 0 + A = A 1.A = A Idempotent  Law A + A = A A.A = A Commutative Law A + B = B + A AB = BA Inverse  Law A + A’ = 1 AA’ = 0 Associative  Law (A + B) + C = A + (B + C) (AB) C Distributive  Law A(B + C) = AB + AC A + BC = (A + B)(A + C) Absorption  Law A + AB = A A(A + B) = A De Morgan’s Law (A + B)’ = A’B’ (AB)’ = A’ + B’

Summary:

## A + AB gets simplified to

After simplification, the value of A+AB will be equal to A.

POPULAR EXAMS
SSC and Bank
Other Exams
GradeStack Learning Pvt. Ltd.Windsor IT Park, Tower - A, 2nd Floor, Sector 125, Noida, Uttar Pradesh 201303 help@byjusexamprep.com